American education - Spring, Joel H. (New York McGraw-Hill, 2012)
"Clear, concise, and authoritative compact and affordable, too with scholarship that is often cited as a primary source, American Education brings up-to-date information and challenging perspectives to teacher educators' classrooms. Revised every two years, American Education provides a fresh, concise, and up-to-date introduction to the historical, political, social, and legal foundations of education and to the profession of teaching in the United States"
Part one-- School and society 1. the history and political goals of public schooling 2. The social goals of schooling 3. education and equality of opportunity 4. The economic goals of schooling: human capital, global economy, and preschool 5. Equality of educational opportunity: race, gender, and special needs 6. Student diversity 7. Multicultural and multilingual education -- Part two-- 8. Local control choice, charter schools,and home schooling 9. Power and control and state and national levels: political party platforms and high-stakes testing 10. The profession of teaching 11. globalization of education.
includes index.
CSSP-8644, CSSP-8645 and CSSP-8646: gift of The Asia Foundation and MoneyGram Foundation.
Keywords: Education -- Social aspects -- United States; Education -- Political aspects -- United States; Educational equalization -- United States; Education and state -- United States